Response of Removal Rates to Various Organic Carbon and Ammonium Loads in Laboratory‐Scale Constructed Wetlands Treating Artificial Wastewater. (1st January 2013) - Wu, Shubiao; Kuschk, Peter; Wiessner, Arndt; Kästner, Matthias; Pang, Changle; Dong, Renjie
Abstract : High levels (92 and 91%) of organic carbon were successfully removed from artificial wastewater by a laboratory‐scale constructed wetland under inflow loads of 670 mg/m 2 d (100 mg/d) and 1600 mg/m 2 d (240 mg/d), respectively. Acidification to pH 3.0 was observed at the low organic carbon load, which further inhibited the denitrification process. An increase in carbon load, however, was associated with a significant elevation of pH to 6.0. In general, sulfate and nitrate reduction were relatively high, with mean levels of 87 and 90%, respectively. However, inhibition of nitrification was initiated with an increase in carbon loads. This effect was probably a result of competition for oxygen by heterotrophic bacteria and an inhibitory effect of sulfide (S 2− ) toxicity (concentration approximately 3 mg/L). In addition, numbers of healthy stalks of Juncus effusus (common rush) decreased from 14 000 to 10 000/m 2 with an increase of sulfide concentration, indicating the negative effect of sulfide toxicity on the wetland plants.